Design and experimental of anti-adhesion rototiller based on staggered double-roller scraping - Cheng, Jian; Xia, Junfang; Zheng, Kan; Liu, Guoyang; Wei, Youshuai; Zou, Juan (International Journal of Agricultural and Biological Engineering, 2024)
In order to solve the serious problem of soil adhering blade roller in the middle and lower reaches of Yangtze River, the anti-adhesion rototiller based on staggered double-roller scraping (ARSDS) was designed by mechanical scraping methods. The volume equation for scraping the soil adhesion part with staggered rotary blades was constructed. The mechanical conditions for separation of soil adhesion part from blade roller were clarified, and the contact time between rotary blade and soil during rotary tillage was analyzed. By this way, the key parameters affecting soil adhering on and separating from the blade roller were determined, which were rotational speed, cutting pitch and tillage depth. The spatial and temporal trajectory changes for the sidelong section edge of staggered rotary blades were analyzed, so that the rotary blade arrangement was obtained. Combining the discrete element method, selecting the soil adhesion mass on the staggered blade rollers as the response value established prediction model by Box-Behnken design test. For example, taking the tillage depth of 14 cm for wheat cultivation in the middle and lower reaches of Yangtze River, the optimal combination of parameters was determined to be 230 r/min and 10 cm for rotational speed and cutting pitch, respectively. At this time, the soil adhesion mass was 4566.67 g. In the meantime, the process of soil particles adhering staggered blade rollers and rotary blades scraping off the adhering soil were clarified. Field experiments have shown that the operation quality of ARSDS met the requirements of rototiller performance indexes. In the rice stubble field of high water moisture, the soil adhesion mass was 13.455 kg and 38.215 kg for ARSDS and conventional rototiller, respectively, which indicated that ARSDS effectively reducing soil adhesion mass. The research results can provide technical support for the design of rototiller reducing soil adhesion in the agricultural areas of the middle and lower reaches of the Yangtze River. Key words: rice stubble field; rotary tillage; reducing soil adhesion; staggered double-roller; discrete element method DOI: 10.25165/j.ijabe.20241703.8002 Citation: Cheng J, Xia J F, Zheng K, Liu G Y, Wei Y S, Zou J. Design and experiment of anti-adhesion rototiller based on staggered double-roller scraping. Int J Agric & Biol Eng, 2024; 17(4): 165–175.